(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The shift towards health-conscious lifestyles has significantly influenced the functional foods market, leading to increased innovation in the development of fermented beverages. Pineapple (Ananas comosus), is recognized for its rich bioactive compounds such as bromelain, and dietary fiber, making their utilization not only nutritionally beneficial but also sustainable. Previous studies have shown that the fusion of pineapple with black tea increased the antioxidant properties of kombucha. However, the effects of pineapple infusion and its by-products on the proximate composition and antioxidant activities of green tea kombucha remain unclear. Therefore, this study aimed to investigate the proximate composition and antioxidant of green tea kombucha when infused with dried pineapple flesh (KPF) and its peels and cores (KPC). The green tea kombucha without any pineapple infusion was used as the control (KT). Proximate composition was analysed using Association of Official Analytical Chemists (AOAC) International standards meanwhile the antioxidant activity was measured using 2,2°-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and Ferric Reducing Antioxidant Power (FRAP) assays. All analyses were conducted on day 13 of fermentation. Findings showed that the infusion with pineapple peels and cores (KPC) in green tea kombucha increased the crude fiber content, probably due to the release of fibrous microparticles during fermentation. Moreover, KPC had significantly the highest antioxidant activity with an IC50 value of 443.9 ug/mL for ABTS and FRAP value of 77.82 μg TEAC/mL compared to other samples. The findings indicate that KPC has a strong potential as a functional ingredient. Future studies could focus on optimizing the formulation to enhance consumer acceptance of pineapple peel-infused green tea kombucha.